AUTHORITIES IN RELIGIOUS CONFLICTS AND CONTROVERSIES: FROM PROBLEMS TO SOLUTIONS (Религиски дијалог и соработка, 2024)
Religious conflicts take place in various ways. This article discusses the role of religionsin low-intensity conflicts occurring in people’s daily lives, relationships, and situations. New skillsare needed to navigate the mosaic of disputes, rights, and obligations. In addition to ordinary citizens,these skills are needed by professionals in different fields who come across issues and peopleassociated with religions. The article examines the role of the public authorities in encountering issues,problems and conflicts related to religions. While the authorities must safeguard the rights ofpeople belonging to religious movements, they also have to solve problems arising from religions.In the article, the authorities’ activities are explored within the framework of religious literacy. Thearticle discusses the basic principles of religious literacy and the ways in which they are manifestedin the context of the authorities’ work. Religious literacy refers interpreting the role of religion indifferent phenomena, institutions, actors, and interactions in society. Understanding, contextualizationand a critical attitude are key components of religious literacy, which could be seen as aprofessional competence that supports authorities and other employees in their work.